Computational approaches for redox potentials of Iron(IV)-oxido complexes - Comba, Peter; Faltermeier, Dieter; Martin, Bodo (Zeitschrift für anorganische und allgemeine Chemie, 2020)
The potential of the redox couple FeIV=O / FeIII-O is of interest for the reactivity of the high-valent nonheme iron oxidants in enzymes and bioinspired small molecule systems but, unfortunately, experimentally it so far is very poorly described. Discussed are three computational methods that are used in combination with available experimental data derived from titrations of FeIV=O species with ferrocene derivatives in dry acetonitrile, and from spectroelectrochemical titrations of FeIII-OH complexes in wet acetonitrile, i.e. describing the FeIV=O / FeIII-OH couple - both data sets are known to have some ambiguities. First, a DFT-based method is used to compute the E° values of 14 FeIV=O / FeIII-O couples with an error margin of around 110 mV. A subset of four species of the original data set is used to evaluate a DLPNO-CCSD(T) based approach, and another subset of complexes, where the spectroelectrochemically determined FeIV=O / FeIII-OH potentials are also known, are used for a Bordwell-Polanyi analysis, which also yield pKa values. It is shown that the three approaches lead to a consistent picture but due to possible ambiguities with the experimental data, it currently is not possible to fully evaluate the accuracy of the used approaches.
Gesehen am 21.04.2023